Ethical Frameworks for AI-Assisted Counseling in the Digital Era - Taufiq Hidayatullah; Tresa Agustian; Ade Sofyan (Yayasan Minang Darussalam, 2025)
Background. The rapid integration of artificial intelligence into mental health and counseling services has transformed traditional counseling practices, offering increased accessibility, scalability, and efficiency in the digital era. AI-assisted counseling systems—such as chatbots, virtual counselors, and decision-support tools—are increasingly used to support psychological well-being. However, their deployment raises complex ethical concerns related to privacy, autonomy, transparency, bias, accountability, and the preservation of human-centered care. Purpose. This study aimed to examine ethical frameworks for AI-assisted counseling in the digital era. Specifically, it analyzed key ethical principles and challenges associated with AI-mediated counseling practices and explored how these principles can be operationalized to ensure ethical integrity, client safety, and professional accountability. Method. A qualitative, conceptual research design was employed using systematic literature analysis and ethical framework synthesis. Data were drawn from peer-reviewed journal articles, professional counseling ethics codes, AI governance guidelines, and policy documents published between 2015 and 2025. The data were analyzed through thematic coding and comparative ethical analysis to identify recurring ethical dimensions and points of convergence across frameworks. Results. The findings indicate that ethical AI-assisted counseling requires the integration of five core principles: respect for client autonomy, data privacy and confidentiality, transparency and explainability of AI systems, fairness and bias mitigation, and shared accountability between human counselors and AI developers. The analysis also reveals gaps between existing counseling ethics codes and emerging AI-specific risks, particularly in informed consent and decision-making authority. Conclusion. Ethical frameworks for AI-assisted counseling must evolve beyond traditional counseling ethics to address the unique challenges posed by intelligent systems. The study highlights the need for interdisciplinary ethical models that combine counseling ethics, AI governance, and human-centered design to support responsible and trustworthy AI integration in digital counseling practices.